Hubungan Pengetahuan, Sikap dan Tindakan Penderita Tuberkulosis dengan Hasil Terapi di Puskesmas Biak Banggai - I Wayan Baliasa; Wulan Pingkan Julia Kaundang; Barnabas Harold Ralph Kairupan (Indonesian Journal of Public Health and Community Medicine, 2020)
Background: Pulmonary tuberculosis (TB) is a direct infectious disease caused by Mycobacterium tuberculosis. In the province of Central Sulawesi, the cure rate and success of pulmonary TB treatment in 2009 to 2012 ranged from 87-88%, this data shows that it has met the national target of> 85%. The purpose of this study was to determine the correlation between the knowledge, attitudes and actions of TB patients with theraupetic of TB. Methods: The research design used in this study was a descriptive analytical study, with a cross sectional approach. The subject in this study were 49 pulmonary tuberculosis patients in 9 villages and 2 sub-districts which were included in the working area of Biak Public Health Center, Luwuk Utara, Banggai Regency. The research instrument used in this study was a questionnaire. Data was analyzed using SPSS with correlation test. Results: The results of this research was showed that there are correlation between knowledge and the results of therapy (p< 0,05; r=0,374). Meanwhile, there is no correlation between attitude and action variables and therapy results. Conclusion: The conclusion of this study is that there a correlation between knowledge about pulmonary TB and the results of therapy. Based on this result, it is necessary to promote the community about TB so that it can increase knowledge about TB.